An alternative treatment of occlusal wear: Cast metal occlusal surface - Sandeep Kumar; Aman Arora; Reena Yadav (Wolters Kluwer Medknow Publications, 2012)
Acrylic resin denture teeth often exhibit rapid occlusal wear, which may lead to decrease in the chewing efficiency, loss of vertical dimension of occlusion, denture instability, temporomandibular joint disturbances, etc. There are various treatment options available like, use of highly cross linked acrylic teeth, amalgam or metal inserts on occlusal surface, use of composite, gold or metal occlusal surface, etc. Several articles have described methods to construct gold and metal occlusal surfaces, however, these methods are time-consuming, expensive and requires many cumbersome steps. These methods also requires the patient to be without the prosthesis for the time during which the laboratory procedures are performed. This article presents a quick, simple and relatively inexpensive procedure for construction of metal occlusal surfaces on complete dentures.